Konsep Spiritual Leadership Menghidupkan Sunnah Harian Nabi Muhammad dalam Pembentukan Karakter SDI di Era Millenial - Muhammad Yusuf Aria Widjaja (STEI Kanjeng Sepuh Gresik Jawa Timur, 2020)
Implementation of Spiritual leadership becomes a challenge in the era of globalization that shows the existence of technological alignments to the dependence of human life. Millennial era, which is the golden generation, is now a cornerstone of every line of management to create a process of organizational activity that runs well. However, now millennial characteristics tend to override spiritual leadership and strive to produce something using mere lust. Spiritual leadership encouragement can be created by realizing it through the daily practice of the Prophet Muhammad's SAW. in order to form the character of a civilized human resource. This paper seeks to answer the challenges of leadership strategy on millennial character so that it can be aligned with organizational goals through the practices of the Prophet Muhammad.